An overview of phytochemicals and potential health-promoting properties of black walnut. Issue 55 (10th September 2020) - Vu, Danh C.; Nguyen, Trang H. D.; Ho, Thi L.
Abstract : Black walnut contains a diverse mixture of bioactive compounds, including phenolics, phytosterols, unsaturated fatty acids, and tocopherols potentially important to human health. Abstract : Black walnut ( Juglans nigra L.) is one of the most widely consumed nuts in the United States. The nut has been recognized for its unique, bold flavor, and used as a versatile food ingredient. The objective of this review is to summarize available research data pertaining to phytochemicals present in black walnut and their previously reported health-promoting properties. Black walnut is rich in phenolics and contains higher levels of phytosterols, unsaturated fatty acids and tocopherols than many other commonly consumed nuts. Dietary intervention of these constituents has been associated with a great number of disease-preventive properties. Black walnut has a potential to inhibit the release of proinflammatory mediators in vitro . Similarities in contents of unsaturated fatty acids and tocopherols between black walnut and English walnut suggest that black walnut consumption may produce beneficial effects on cardiovascular disease risks. In addition, the high level of γ-tocopherol in black walnut could make the nut a cancer-preventive option. Although evidence has shown black walnut kernel is a rich source of phytochemicals of potential importance to human health, there is a paucity of in vitro and in vivo studies on the bioactivities of these phytochemicals isolated from black walnut and the health-promoting properties of black walnut consumption. Clinical studies are needed to better understand the health benefits of black walnut.